Eye Flu - Way to Conquer With General and Homoeopathic Measures (Homoeopathy for All, 2023)
Eye flu, medically known as  conjunctivitis, is a common eye  condition that affects people of all ages.  It is characterized by inflammation of  the conjunctiva, the thin, transparent  layer covering the white part of the  eyes and the inner surface of the  eyelids. Understanding the eye flu  causes is crucial in preventing its  spread and ensuring timely treatment.  This article provides an overview  of the aetiology, diagnosis, and  appropriate general & homoeopathic  management for conjunctivitis.
Keywords: Eye Flu; Conquer